(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
Adaptive deficits are commonly found in high functioning autism spectrum disorders (HF-ASD) despite of cognitive potential. Most studies have focused on the relationships between adaptive behavior and intellectual quotient (IQ) and have used correlations to study relationships between them. Few studies have analyzed cognitive variables other than IQ as potential predictors of adaptive behavior in HF-ASD using regression methods. This study aimed to analyze the impact of several cognitive variables on adaptive behavior in a sample of children and adolescents with HF-ASD. METHODS: Sample included 16 child and adolescent boys with HF-ASD (age between 7-17 years). Cognitive assessment included measures of general intelligence, visual memory, verbal memory, working memory and problem solving/flexibility tests. Vineland Adaptive Behavior Scales (VABS) was used to evaluate adaptive behavior. To establish the predictive capacity of the cognitive variables for adaptive functioning, linear regression models were fitted for each adaptive domain using a stepwise method. RESULTS: Verbal memory and IQ emerged as the main independent predictors for VABS adaptive scores. The 41% of the variance in Communication was predicted by IQ. The 35% of the variance in Daily Living Skills was predicted by verbal memory. Almost half of the variance in Socialization was predicted by both, verbal memory and IQ (49%). No other cognitive functions were associated with adaptive scores. CONCLUSIONS: The results highlight the strong impact of IQ and verbal memory on adaptive behavior in HF-ASD patients. These findings could contribute to identify potential targets of intervention.